2011
DOI: 10.1620/tjem.224.7
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Induces Osteogenesis-Related Activities and Expression of Core Binding Factor .ALPHA.1 in Mesenchymal Stem Cells

Abstract: Mesenchymal stem sells (MSCs) have received much attention in the field of bone tissue engineering due to their biological capability to differentiate into osteogenic lineage cells. Hypoxia-inducible factor 1alpha (HIF-1α) plays an important role in the MSC-related bone regeneration during hypoxia, while core binding factor alpha 1 (Cbfα1) is a transcription regulator that is involved in the chondrocyte differentiation and ossification. In the present study, we investigated the effects of hypoxia on biological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 24 publications
1
19
0
Order By: Relevance
“…The expression patterns of HIF-1α protein and the osteogenic markers (Runx2 and ALP activity) were consistent with that of HIF1A-AS1 and HIF1A-AS2. HIF-1α mRNA was highly expressed under hypoxia and then declined gradually after 6 h. In addition, Huang et al (31) also observed that HIF-1α mRNA was elevated at 1 h and peaked at 6 h under hypoxia in human mesenchymal stem cells (hMScs), and then the level was gradually declined from 6 to 24 h. Uchida et al (20) found that HIF-1α protein was highly induced during the first few hours in hypoxia, regulated by translation or post-translation pathways, and inhibited in prolonged hypoxia due to the decline in HIF-1α mRNA. With respect to the osteogenic differentiation ability under hypoxia, Wu et al (32) demonstrated that Runx2 mRNA and protein were immediately enhanced from 1 h and ALP activity was from 3 h in PdLScs when exposed to hypoxia, and they still remained higher than the normoxia group at 24 h. Furthermore, ding et al (33) found that continuous hypoxia after 3 days impaired the osteogenenic differentiation of hMScs in hypoxia.…”
Section: Discussionmentioning
confidence: 97%
“…The expression patterns of HIF-1α protein and the osteogenic markers (Runx2 and ALP activity) were consistent with that of HIF1A-AS1 and HIF1A-AS2. HIF-1α mRNA was highly expressed under hypoxia and then declined gradually after 6 h. In addition, Huang et al (31) also observed that HIF-1α mRNA was elevated at 1 h and peaked at 6 h under hypoxia in human mesenchymal stem cells (hMScs), and then the level was gradually declined from 6 to 24 h. Uchida et al (20) found that HIF-1α protein was highly induced during the first few hours in hypoxia, regulated by translation or post-translation pathways, and inhibited in prolonged hypoxia due to the decline in HIF-1α mRNA. With respect to the osteogenic differentiation ability under hypoxia, Wu et al (32) demonstrated that Runx2 mRNA and protein were immediately enhanced from 1 h and ALP activity was from 3 h in PdLScs when exposed to hypoxia, and they still remained higher than the normoxia group at 24 h. Furthermore, ding et al (33) found that continuous hypoxia after 3 days impaired the osteogenenic differentiation of hMScs in hypoxia.…”
Section: Discussionmentioning
confidence: 97%
“…In bone marrow-derived MSCs, hypoxia gradually increases the expression of CBF-1α, which enhances the potential of MSCs to differentiate into osteocytes (Huang et al, 2011). CBF-1α is regulated by the Notch signaling pathway, which promotes the formation of Notch intracellular domain (NICD).…”
Section: Introductionmentioning
confidence: 99%
“…This improvement was also found in the HIF‐1α transduced rat BM‐MSCs with higher level of angiogenic and osteogenic gene expression [Zou et al, 2011]. Similar result was documented in rabbit BM‐MSCs [Huang et al, 2011]. However, the opposite result was observed in human BM‐MSCs which showed that HIF‐1α was implicated in the down‐regulation of osteogenesis by Betacellulin [Genetos et al, 2010].…”
Section: Discussionmentioning
confidence: 53%